PIM findings used to develop the United States Government's strategy in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2018)
USAID used PIM research on growth and transformation, value chains and youth employment to frame challenges and opportunities in the Global Food Security Strategy Ethiopia Country Plan for 2018-2023, which serves as an overarching framework for integrated food security and nutrition programming.